The Urgency of Returning the People's Consultative Assembly Authority in Determining the Outlines of the Nation's Direction - Noer Wahid, Deny; Anggraeny, Isdian; Samira Echaib (Universitas Airlangga, 2023)
The role of the MPR after the amendments to the 1945 Constitution carried out in the reform era has reduced most of the power of the MPR which was originally as an implementation of people's sovereignty, as stipulated in Article 1 paragraph (2) of the 1945 Constitution. As a result, the MPR of the Republic of Indonesia showed that as an permanent state high institution, although they continue to function as ad hoc organizations. Furthermore, the government's development became unsure and tended to be chaotic after the Indonesian People's Consultative Assembly abolished the power to define the country's direction, prioritizing only the five-year political program. By placing restrictions on the drafting of these provisions, restoring the People's Consultative Assembly of the Republic of Indonesia's power to make decisions, it is hoped that it will become a function of social control of the Citizen. Based on the description above, the following problems are formulated: 1. The urgency of returning the MPR's role to make decisions as a function of citizen social control. 2 Restore the authority of the MPR to make the outlines of the nation's direction as a guideline for state development. In order to discuss this, a historical approach, a statutory approach, and a conceptual approach are combined with a normative legal research methodology.